From Silence to Confidence: Improving Students’ Speaking through Word Card Media - Maya Rizki Amalyasari; Orny Karnuara Mburu; Hernina Dewi Lestari (Sumber Belajar Sejahtera, 2025)
Speaking is one of the most essential yet challenging skills for language learners, especially when limited vocabulary and low confidence restrict their ability to communicate effectively. This Classroom Action Research (CAR) aimed to enhance students’ English-speaking skills through the use of word card media. The study involved 15 seventh-grade students of class VII A and followed four stages: planning, acting, observing, and reflecting. Data were collected through tests, observations, interviews, and questionnaires using both quantitative and qualitative analyses. Before the intervention, students showed low confidence, poor vocabulary mastery, and minimal participation. After implementing word card media, students became more active and confident in speaking activities. The mean speaking score increased from 71 to 80, surpassing the Minimum Mastery Criteria. Observations and questionnaire results (overall mean = 3.44) indicated higher motivation, engagement, and positive perceptions of the learning process. The findings demonstrate that word card media effectively improve vocabulary mastery, pronunciation, fluency, and confidence, while transforming the classroom into a more student-centered and interactive environment. This study also introduces a new concept of multimodal, vocabulary-driven speaking instruction, in which word cards act as interactive cognitive tools that bridge vocabulary learning and communicative use. Future research is recommended to explore digital or gamified word card applications to enhance personalized and engaging speaking practice in various educational contexts.